IMPACT OF CLASSROOM MANAGEMENT ON STUDENTS ENGAGEMENT AND LEARNING OUTCOMES IN SELECTED NIGERIAN SECONDARY SCIENCE CLASSES - ONYIMONYI, CHILEE C. ONWUKWE; AGI , KABIRU Musa; NAMO, DANJUMA (Sokoto Educational Review, 2025)
This study investigates the impact of classroom management on student engagement and learning outcomes in Nigerian secondary school science classes. The research adopted a mixed-methods approach, combining quantitative data from student and teacher questionnaires with qualitative insights from classroom observations and academic performance records. A total of 500 science students and 30 science teachers were sampled from ten public secondary schools across diverse regions in Nigeria. The study focused on three key aspects of classroom management: classroom rules and routines, teacher-student relationships, and the use of interactive teaching methods. Multiple regression analyses revealed that these variables significantly predicted both student engagement and academic achievement in science subjects. Specifically, classroom management practices accounted for 52% of the variance in student engagement and 47% of the variance in science learning outcomes. Findings underscore the importance of structured and student-centered classroom environments in enhancing learning in science education. The study concludes that effective classroom management not only promotes discipline and order but also serves as a catalyst for improved student participation and academic performance. It recommends targeted teacher training, policy support, and the integration of interactive pedagogical strategies to strengthen science education in Nigerian schools. DOI: https://doie.org/10.10318/SER.2025937325